Language Arts Guide Composition and Language Study. Junior High School. - Dade County Board of Public Instruction, Miami, FL.; Dade County Board of Public Instruction, Miami, FL. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1968)
GRADES OR AGES: Junior high school (grades 7, 8 and 9). SUBJECT MATTER: Language arts; composition and language study. ORGANIZATION AND PHYSICAL APPEARANCE: The guide has three main sections: 1) oral composition--individual preservations and group activities; 2) language study--the nature of language, varieties of language, history of the English language, kernel sentences, and transforms; and 3) written composition--word rhetoric, sentence rhetoric, basic thought processes, principles of rhetoric, and assignments. The material in each section is sequential and not defined specifically in terms of grades. The guide is lithographed, with perfect binding and a soft cover. OBJECTIVES AND ACTIVITIES: Objectives are not listed separately, but are an integral part of the introductory material for each unit. Activities are given in detail for each unit. INSTRUCTIONAL MATERIALS: Materials needed are listed at the end of each unit and include records, films, and books for teachers and students. STUDENT ASSESSMENT: No specific provision is made for evalution. (MBM)
Availability: Textbook Dept., Board of Public Instruction, 2210 S.W. 3 Street, Miami, Fla. 33135 ($1.00).
ERIC Note: Curriculum Bulletin No. 6H.
Educational level discussed: Grade 7.
Educational level discussed: Grade 8.
Educational level discussed: Grade 9.
Educational level discussed: Junior High Schools.
Keywords: Curriculum Guides; English; Grade 7.; Grade 8.; Grade 9.; Junior High Schools; Language Arts; Oral English; Speech Communication; Writing (Composition)